Response of Nutrient Management to Growth, Yield and Economics of Pigeonpea+Radish Intercropping System in Odisha - Sethy, A. K.; Barik, A. K.; Paikaray, R. K. (International Journal of Bio-resource and Stress Management, 2019)
A field experiment was conducted to study the growth and productivity of pigeonpea + radish intercropping system under different nutrient management practices for two consecutive years during kharif seasons of 2013 and 2014 at Instructional Farm, RRTTS, Gumusur Udayagiri, OUAT, Kandhamal, Odisha, India. The treatments were Pigeonpea (100% RDF)+Radish (100% RDF), Pigeonpea (100% RDF)+Radish (75% RDF), Pigeonpea (100% RDF)+Radish (50% RDF), Pigeonpea (100% RDF)+Radish (25% RDF), Pigeonpea (100% RDF)+Radish (0% RDF ), Pigeonpea (75% RDF)+Radish (100% RDF), Pigeonpea (50% RDF)+Radish (100% RDF ), Pigeonpea (25% RDF)+Radish (100% RDF), Pigeonpea (0% RDF)+Radish (100% RDF), Pigeonpea (0% RDF)+Radish (0% RDF) as control, sole Pigeonpea (100% RDF) and Sole Radish (100% RDF).The twelve treatments were replicated thrice in a randomized block design. Among the intercropping systems, the treatment 100% RDF was applied to the base crop (pigeonpea) and 100% RDF to the intercrop (radish) almost all the growth parameters as well as yield components showed highest values. Sole crop of pigeonpea with 100% RDF produced the highest seed yield (1.20 t ha-1) and stover yield (4.56 t ha-1). Sole radish crop with 100% RDF achieved the highest root yield (17.70 t ha-1) and leaf yield (4.02 t ha-1) over other treatments followed by pigeonpea + radish with 100% RDF to base crop+100% RDF to intercrop. Sole radish exhibited the highest net return (` 73773 ha-1) and return rupee-1 investment (3.28) with 100% RDF though the highest gross return (` 125890 ha-1) was obtained from pigeonpea +radish intercropping system with 100% RDF to both the crops.